MODELING ROBOTECHNICAL MECHATRONIC COMPLEXES IN V-REP PROGRAM - Yesmakhanova, Laura (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2024)
The article clarifies the issues of modeling robotic systems in the V-REP program and provides skills in modeling the process of robotic and mechatronic complexes operation taking into account the laws of physics. The aim of the research paper is to investigate a 3D robotic simulator based on a distributed control architecture: control programs (or scripts) can be directly attached to objects in the scene and executed simultaneously in a streaming or non-streaming mode. V-REP can be used for remote monitoring, for hardware control, for rapid prototyping and verification, for rapid algorithm development/parameter tuning, for safety retesting, for robotics education, factory automation simulation, etc.